2017
DOI: 10.1007/978-3-319-22801-3_1
|View full text |Cite
|
Sign up to set email alerts
|

Embedded Clusters

Abstract: The past decade has seen an increase of star formation studies made at the molecular cloud scale, motivated mostly by the deployment of a wealth of sensitive infrared telescopes and instruments. Embedded clusters, long recognised as the basic units of coherent star formation in molecular clouds, are now seen to inhabit preferentially cluster complexes tens of parsecs across. This chapter gives an overview of some important properties of the embedded clusters in these complexes and of the complexes themselves, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 162 publications
0
2
0
Order By: Relevance
“…To assess the strength of hierarchical versus radial distributions of YSOs in these clustering, we estimated the Q parameter. It is defined as the ratio of the normalized mean MST branch ( lMST ) to the normalized mean separation (s) between objects (refer to Schmeja & Klessen 2006;Chavarría et al 2014;Ascenso 2018),…”
Section: Physical Properties Of the Stellar Clustering In The Regionmentioning
confidence: 99%
“…To assess the strength of hierarchical versus radial distributions of YSOs in these clustering, we estimated the Q parameter. It is defined as the ratio of the normalized mean MST branch ( lMST ) to the normalized mean separation (s) between objects (refer to Schmeja & Klessen 2006;Chavarría et al 2014;Ascenso 2018),…”
Section: Physical Properties Of the Stellar Clustering In The Regionmentioning
confidence: 99%
“…In the competitive accretion model, the initial condition is a massive cloud-star system of more than a few 1000 M ⊙ where individual stars compete to acquire mass gravitationally, whereas the model fails to explain the formation of an isolated small-mass system including isolated one or a few O stars which are distributed widely in the Galaxy (for a review see Fukui et al 2021a; see also, Ascenso 2018). The monolithic collapse model assumes an initial condition "a massive gas cloud of 100 M ⊙ within a radius of 0.1 pc", which matches the 1 g cm −2 criterion, and it was numerically demonstrated that high-mass stars of 40 M ⊙ and 30 M ⊙ in a binary are formed (Krumholz et al 2009).…”
Section: High-mass Star Formationmentioning
confidence: 99%